Henry James and Homo-Erotic Desire
XIV, 153 p.
Keywords: Sheldon M. Novick has written an extensive biographical introduction. This is complimented by an essay documenting James's friendships with younger men, which includes quotations from unpublished letters. Other subjects include the influence on James of the emergence of a specific concept of 'the homosexual' and James's reactions to the aesthetic movement; and there are close analyses of many of James's stories and novels, selected so that all of his career is represented.